1999
DOI: 10.1080/1355800990360409
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ Experiences of Using the World Wide Web as an Information Resource

Abstract: This paper describes a study we have made of undergraduates' experiences of using the World Wide Web as an adjunct information resource. The focus of the research was not on students using information provided by academic staff nor on any form of computer-aided learning, but rather, on the information sought and used by students which was freely available on the Web. In a series of interviews, 12 undergraduate students related their experiences of using the Web as a resource to support their studies. The quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The lack of confidence in search engines provides insight into possible reasons why students may be reluctant to use the web in the first place. Hall and Dalgleish (1999) reported a similar finding in a much smaller study some five years ago, which showed undergraduates' frustrations with search engines. It is interesting and somewhat disappointing to note the distinct lack of progress and ongoing dissatisfaction with achieving quality results in the use of search engines for study purposes and this continues to be the case despite earlier calls for good quality, dedicated search engines (Newton, Marcella & Middleton, 1998).…”
Section: The Question Of Qualitysupporting
confidence: 64%
“…The lack of confidence in search engines provides insight into possible reasons why students may be reluctant to use the web in the first place. Hall and Dalgleish (1999) reported a similar finding in a much smaller study some five years ago, which showed undergraduates' frustrations with search engines. It is interesting and somewhat disappointing to note the distinct lack of progress and ongoing dissatisfaction with achieving quality results in the use of search engines for study purposes and this continues to be the case despite earlier calls for good quality, dedicated search engines (Newton, Marcella & Middleton, 1998).…”
Section: The Question Of Qualitysupporting
confidence: 64%
“…Prior research consistently shows that web-based peer feedback methods have been advantageous as compared to traditional forms of feedback (Liu, Lin, Chiu, & Yuan, 2001). The immediacy and flexibility afforded by web technologies has enabled learners to provide more frequent and timely feedback without the constraints of time and space (Augustsson, 2010;Everhart, 2006;Hall & Dalgleish, 1999;Tsai, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Students develop and deploy such skills within a course context where they are also engaged in learning the subject and learning how to learn. Hall and Dalgleish (1999) illustrate how students frame their information seeking from the Web according to the perceived course demands. Accessing and using information resources is one of the ways in which students begin to act as independent learners, becoming involved in making choices, weighing evidence and coming to conclusions for themselves.…”
Section: Introductionmentioning
confidence: 99%